FOLLOW-UP IN EDUCATION OF RESPONSIBILITY IN SENIOR PRESCHOOL AND JUNIOR SCHOOLCHILDREN - R.V. Kondratenko (Academy of Cognitive and Natural Sciences, 2022)
The author describes the issues of effective implementation of continuity in the education of responsibility for children in preschools and primary schools.